Re-enactment leading to transformation: A critical assessment of the distinctives of Pentecostal preaching - Nel, Marius (Stellenbosch Theological Journal, 2017)
The article aims to define what the most distinctive characteristics of Pentecostal preaching are in order to assess these elements critically. Pentecostal preachers argue that their message is concerned with the Bible as the Word of God and its explication for modern-day listeners, but with the explicit purpose to perpetuate what the Bible says about the revelation of God as revealed to the contemporary preacher. The purpose of preaching is in other words that believers will experience an encounter with the same Spirit who revealed God to people in biblical times in order that present-day people will be saved, freed, healed and delivered in the same way as in apostolic times. Pentecostal preaching is described in terms of three elements, God’s work in preaching, preparation for preaching, and the preaching event. The several aspects are described and discussed and some of the conclusions are that Pentecostal preaching should as non-negotiable be rooted soundly in Scripture, beginning from and focusing on the biblical text, while at the same time exegesis, although necessary academic work, may not be allowed to minimize the influence of the Spirit because the end of preaching is a word from God that produces the divine desired effect in the human situation. However, the emphasis on supernatural results leads in some instances to the manipulation of the context of preaching in order to gain the desired results, using emotionalism, mass suggestion, disorder, or showmanship.